The development of lectora inspires media in learning mathematics fractions material - Asih Mardati; Lina Annisa; Yeyen Febrilia; Desfa Yusmaliana (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
This research aims to consider pointed to decide the steps in creating Lectora Inspire learning media and its possibility for arithmetic learning of divisions for third-grade basic school understudies. The investigation was investigation and improvement. The advancement forms concerned the improvement show proposed by Thiagarajan's 4D. The 4D development model included the stages of (1) Define, (2) Design, (3) Development, and (4) Dissemination. The information collection rebellious utilized were master appraisal sheets, instructor evaluation sheets, and understudy appraisal sheets. The result about appeared that Lectora inspire media gotten a rate of 77.3% within the "great" category by media specialists, 88% within the "outstanding" category by material specialists, and 86.6% within the "extraordinary" category by learning specialists. The normal rate from specialists was 83.96%. The result of the teacher's appraisal gotten a rate of 96% within the "exceptional" category. The result of the restricted trial evaluation gotten a rate of 100% within the "exceptional" category. This information demonstrated that the Lectora inspire media for arithmetic learning of divisions for third-grade understudies of the rudimentary school had a fabulous and doable quality. These data indicated that the Lectora Inspire media for mathematics learning of fractions for third-grade students of elementary school had an excellent quality and was feasible.